2017
DOI: 10.1111/ggi.13126
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycation and anti‐oxidant efficiency of carnosine in the plasma and liver of aged rats

Abstract: These results clearly show that CAR might be useful for decreasing glycoxidant stress in aged rats. Geriatr Gerontol Int 2017; 17: 2610-2614.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Kuloglu et al (19) reported that rats that received carbon tetrachloride exhibited significantly higher ALT and AST levels than rats administered carbon tetrachloride and CAR. Similarly, Tokyol et al (24) reported increased ALT and AST levels after hepatic I/R, which suggested free-radical-induced hepatic tissue damage; and these increases were ameliorated by CAR. In our study, the increases in AST and ALT levels caused by I/R damage were significantly ameliorated by CAR pretreatment.…”
Section: Discussionmentioning
confidence: 87%
“…Kuloglu et al (19) reported that rats that received carbon tetrachloride exhibited significantly higher ALT and AST levels than rats administered carbon tetrachloride and CAR. Similarly, Tokyol et al (24) reported increased ALT and AST levels after hepatic I/R, which suggested free-radical-induced hepatic tissue damage; and these increases were ameliorated by CAR. In our study, the increases in AST and ALT levels caused by I/R damage were significantly ameliorated by CAR pretreatment.…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence, first obtained more than 25 years ago, that carnosine delays senescence, extends lifespan and even rejuvenates cultured human lung fibroblasts [5]. Subsequent studies revealed that carnosine (i) can delay ageing and/or related phenomena in some animal models [6][7][8][9][10], (ii) possesses anti-oxidant and anti-glycating activities [11][12][13][14][15], (iii) possesses anti-inflammatory properties [16][17][18][19][20], (iv) is protective towards lung injury [21][22][23], (v) can decrease the infectivity of RNA viruses Zika, Denge [24] and influenza [25], (vi) is an inhibitor of CD26 (also known and dipeptidyl peptidase IV (DPP4) [26,27] and ACE-2 (angiotensin converting enzyme 2) [28,29], i.e. the cell receptors to which COVID-19 attaches to ensure infection [30,31], (vii) can complex with zinc ions to form polaprezinc [32]; it has been reported that zinc ions can inhibit COVID-19 RNA polymerase thus suppressing viral replication [33].…”
Section: Carnosine Aging and Covid-19mentioning
confidence: 99%
“…Childhood trauma has been linked to psychopathology, accelerated aging-related DNA methylation [42] and schizophrenia [43]. Furthermore, erythrocytes from schizophrenics show evidence of increased aging-related protein glycation [44], while dietary carnosine supplementation has been shown to produce beneficial effects in schizophrenics [45], possibly due, in part, to carnosine's anti-glycating activity [11,12].…”
Section: Carnosine and Bloodmentioning
confidence: 99%
“…The ingestion of carnosine was also determined to exert a therapeutic effect on chronic metabolic disorders, a property which is likely associated with its potent anti-oxidative, anti-glycation, Carnosine-a natural bioactive dipeptide Xing et al Aged rats ↓AGE and MDA; ↓Protein carbonyl and advanced oxidized protein products Bingül et al, 2017 Anti-inflammatory Caco-2 cells ↓IL-8 secretion Son et al, 2008 Male Balb/cA mice ↓c-reactive protein (CRP), IL-6 tumor and TNF-α Liu et al, 2008 Balb/cA mice ↓IL-6, TNF-α, and MCP-1 Yan et al, 2009 Mice ↓TNF-α and IL-6 levels Tsai et al, 2010 Elderly people ↓MCP-1 and IL-8 Hisatsune et al, 2016 Sepsis-induced male albino rats.…”
Section: Heath Benefitsmentioning
confidence: 99%